SAT0343 How Much Does Fatigue Contribute to the Physician and Patient Global Estimates in Different Rheumatic Diseases? Analysis from Routine Care on a Multidimensional Health Assessment Questionnaire (MDHAQ). (9th June 2015) - Castrejon, I.; Nikiphorou, E.; Jain, R.; Huang, A.; Block, J.A.; Pincus, T.
Abstract : Background: Fatigue is an important problem for many patients with rheumatic diseases. Fatigue has been associated with disease severity, psychological distress, and a poorer quality of life in rheumatoid arthritis (RA) [1]. Although an important symptom for patients, it is controversial how much fatigue may contribute to the level of disease activity. Objectives: To evaluate possible associations between fatigue and global estimates of disease activity according to the patient and the physician in patients with different rheumatic diseases. Methods: All patients seen in one academic clinical setting complete a multidimensional health assessment questionnaire (MDHAQ) in 5-10 minutes in the waiting area, prior to seeing the rheumatologist in the infrastructure of usual care. The two-page MDHAQ includes physical function (FN) in 10 activities of daily living, three 0-10 visual analog scale (VAS) for pain (PN), patient global estimate (PATGL), and fatigue (FT), and demographic data. PATGL and physician global estimate (DOCGL) were used to define four disease activity categories at the following predefined levels: <1 for "inactive disease", 1-3 for "low", 3-6 for "moderate", and >6 for "high". Median values for fatigue and interquartile range (IQR) were compared in 4 categories according to 4 diagnoses: rheumatoid arthritis (RA), osteoarthritis (OA), systemic lupus erythematosus (SLE), and fibromyalgia (FM). Results: Analyses included 612 consecutive patients, 173 with RA, 199 with OA, 146 with SLE and 94 with FM. Median fatigue score was significantly higher in FM (7, IQR=5-8) p<0.001, but similar in RA (4, IQR=1-7), OA (5, IQR=2-7.5), and SLE (5, IQR=1.5-7.5). Fatigue scores were significantly higher according to disease activity categories in RA, OA and SLE patients, as reported by the patients and by the DOCGL, suggesting associations with diseases that are characterized by structural involvement of the musculoskeletal system (Table ). In contrast, this pattern was not observed in patients with FM. Conclusions: Fatigue scores are associated with severity of disease activity in structural conditions such as RA, OA, and SLE, but do not appear to be similarly associated in myofascial pain syndromes. This is evident both from the physician's and from the patient's perspective. Fatigue is a relevant and important symptom, which can be collected in the infrastructure of routine care as a quantitative VAS on an MDHAQ in patients with all rheumatic diagnoses. References: Nikolaus S, Bode C, Taal E, et al. Fatigue and factors related to fatigue in rheumatoid arthritis: a systematic review. Arthritis Care Res (Hoboken) 2013; 65:1128-46 Disclosure of Interest: None declared